Pengetahuan Dan Kesiapsiagaan Masyarakat Menghadapi Bencana Banjir Di Bolapapu Kecamatan Kulawi Sigi Sulawesi Tengah - Umar, Nurlailah (Jurusan Keperawatan FIKES UNSOED, 2013)
Preparedness in facing the flood helps the community in forming and planning actions that need to do when flood happen. This research aims to obtain a knowledge description and community preparedness in facing flood disaster in Bolapapu Village Kulawi District Regency of Sigi Central Sulawesi. It used qualitative design with a phenomenological approach. Informants in this research were people who had ever experienced flooding. Informants retrieval technique used purpossive sampling then continued by snow ball method. The number of informants were 12 people. The data collection was used observations, interviews and documentations. It was analyzed by qulitative with inductive method. The result of this research showed that from all informants there were some of them did not know about flood. Community did not have readiness and steps yet that should be done before, during and after flood disaster. Community should be given an education and a training of preparedness in facing flood disaster. For related parties in order to continue campaignto comunity about knowledge and ways of facing flood disaster. Such as what steps should be done before, during and after flood disaster are. In handling the flood, and to community should payed attention to the steps before, during and after flood disaster.